Synthesis of automotive cams using multiple shooting-SQP methods for constrained optimization - Bock, Hans Georg; Schlöder, Johannes P.; Winckler, Michael J. (Mathematics - key technology for the future, 2003)
Cam design is an old field of mechanical engineering. Because of the complexity of the problem, design procedures have emphasized the use of standardized approaches and rules-of-thumb, which produce reasonable designs without attempting to obtain a truly optimized performance. Increased competition among manufacturers puts pressure on designers to find new ways to deal with the complexity of the problem In recent years progress in the mathematics of numerical solution of optimal control problems has made it possible to obtain numerical solutions for these problems using realistic models and the needed highly nonlinear state inequality constraints. The work reported here develops a high level user interface for cam system designers as well as researchers in the field. It makes available sophisticated numerical integration that handles the necessary discontinuities, and numerical optimization with SQP methods to handle the complex optimization criteria and side conditions. This forms a tool for interactively designing cam systems to create optimal trade offs between the multiple performance characteristics of importance.